1971
DOI: 10.1007/bf02287084
|View full text |Cite
|
Sign up to set email alerts
|

Pygmalion revisited: A loud call for caution

Abstract: The concept of the teacher expectancy effect continues to have a major impact on educational and psychological thinking. This article reviews the literature and concludes that the teacher expectancy effect, like the experimenter expectancy effect, is more difficult to demonstrate and less pervasive than has been claimed. It suggests that the most relevant issue is determining the relevant child characteristics that significantly cause a particular teacher to form an expectation about a particular child.L'effet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

1972
1972
1983
1983

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Women tended to lean forward more often than the men. These results are consistent with earlier studies with adult, white subject populations, showing that women maintain less spatial distance than men during social interaction (see Harper, Wiens, & Matarazzo, 1978, for a literature review). In a related experiment (Chaikin & Derlega, 1978), white women were more expressive facially than white men in terms of frequency of smiling, frowning, and laughmg (which are kinesic behaviors).…”
Section: Subjects 'Sexsupporting
confidence: 92%
See 1 more Smart Citation
“…Women tended to lean forward more often than the men. These results are consistent with earlier studies with adult, white subject populations, showing that women maintain less spatial distance than men during social interaction (see Harper, Wiens, & Matarazzo, 1978, for a literature review). In a related experiment (Chaikin & Derlega, 1978), white women were more expressive facially than white men in terms of frequency of smiling, frowning, and laughmg (which are kinesic behaviors).…”
Section: Subjects 'Sexsupporting
confidence: 92%
“…Differences between the gain scores of the bloomer and the control groups were greatest in the first two grades. Though critics have questioned these results (e.g., Claiborne, 1969;Elashoff & Snow, 1971;Grieger, 1971; Thorndike, 1968), many studies have confirmed that teacher expectancies influence student performance (see Brophy & Good, 1974;Gerard & Miller, 1975;Jones, 1978;Rosenthal, 1974;Rosenthal & Rubin, 1978).…”
mentioning
confidence: 99%
“…By implication, the study also seemed to support claims made by critics of the schools that the lower academic achievement of poor and minority group pupils was largely the result of the negative stereotypes and low expectations of their teachers. While the initial Rosenthal and Jacobson (1968) study has been strongly criticised (e.g., Thorndike, 1968; Elashoff and Snow, 1971; Greiger, 1971) it sparked off numerous studies of teacher expectations during the following decade. From investigations using a The paper was written while the author was visiting in the Department of Education, Washington State University.…”
Section: Introductionmentioning
confidence: 99%
“…Αυτό που ο Bernstein τονίζει, είναι ότι ο μαθητής -κάτοχος του «περιορισμένου γλωσσικού κώδικα» βιώνει τη σχολική εμπειρία ως συμβολική και κοινωνική αλλαγή, σε αντίθεση με το μαθητή -κάτοχο του «επεξεργασμένου γλωσσικού κώδικα», ο οποίος βιώνει τη σχολική διαδικασία ως συμβολική και κοινωνική εξέλιξη. Η πρώτη περίπτωση παραπέμπει σε αλλαγή της κοινωνικής ταυτότητας του παιδιού, ενώ η δεύτερη σε ανάπτυξή της 79 .…”
unclassified
“…23 -38. 79 Βλ. Bernstein, B., "A socio -linguistic approach to socialization: With some reference to educability" pp.…”
mentioning
confidence: 99%